SARS‐CoV‐2‐specific serological and functional T cell immune responses during acute and early COVID‐19 convalescence in solid organ transplant patients. Issue 8 (12th April 2021) - Favà, Alexandre; Donadeu, Laura; Sabé, Nuria; Pernin, Vincent; González‐Costello, José; Lladó, Laura; Meneghini, Maria; Charmetant, Xavier; García‐Romero, Elena; Cachero, Alba; Torija, Alba; Rodriguez‐Urquia, Ronny; et al.
Abstract : The description of protective humoral and T cell immune responses specific against SARS‐CoV‐2 has been reported among immunocompetent (IC) individuals developing COVID‐19 infection. However, its characterization and determinants of poorer outcomes among the at‐risk solid organ transplant (SOT) patient population have not been thoroughly investigated. Cytokine‐producing T cell responses, such as IFN‐γ, IL‐2, IFN‐γ/IL‐2, IL‐6, IL‐21, and IL‐5, against main immunogenic SARS‐CoV‐2 antigens and IgM/IgG serological immunity were tracked in SOT ( n = 28) during acute infection and at two consecutive time points over the following 40 days of convalescence and were compared to matched IC ( n = 16) patients admitted with similar moderate/severe COVID‐19. We describe the development of a robust serological and functional T cell immune responses against SARS‐CoV‐2 among SOT patients, similar to IC patients during early convalescence. However, at the infection onset, SOT displayed lower IgG seroconversion rates (77% vs. 100%; p = .044), despite no differences on IgG titers, and a trend toward decreased SARS‐CoV‐2‐reactive T cell frequencies, especially against the membrane protein (7 [0–34] vs. 113 [15–245], p = .011, 2 [0–9] vs. 45 [5–74], p = .009, and 0 [0–2] vs. 13 [1–24], p = .020, IFN‐γ, IL‐2, and IFN‐γ/IL‐2 spots, respectively). In summary, our data suggest that despite a certain initial delay, SOT population achieve comparable functional immune responses than the general population after moderate/severe COVID‐19. Abstract : Solid organ transplant patients achieve robust adaptive immune responses after a moderate to severe COVID‐19 infection, although with a functional delay compared to immunocompetent individuals.